Analisis Analisis Laporan Keuangan untuk Mengukur Kinerja Keuangan atas Penyaluran Kredit PT BTN (persero) Tbk - Riza Amalia Rifani (Amsir Management Journal, 2021)
Analysis of financial statements with financial ratios can help business people, investors, the government, and other stakeholders in assessing the financial condition and performance of banks. The purpose of the study was to determine the financial performance in terms of providing credit at PT. BTN (Persero) Tbk. The analytical method used is the descriptive analysis by analyzing using several methods of financial statement ratios to measure the bank's financial performance on lending at PT. Bank Tabungan Negara Tbk Makassar from 2016 to 2020. The ratios used are the liquidity ratio (LDR), capital adequacy ratio (CAR), profitability ratio (ROA), and non-performing loan (NPL) ratio. The results showed that LDR was at the highest level of 107.74% in the 2019 period. The high lending caused bank loans to grow higher than the growth of third-party funds. (CAR) is in a very good range, which is around 15-20%. The higher the CAR, the better the performance of the bank's capital adequacy. Banks can minimize risk. (ROA) which was in an up and down status, namely in 2019 it recorded the lowest level of 0.2% from 2018 which was at 1.2%, indicating declining profits and assets, and (NPL) for the 2016-2020 period was at 1.2%. at a good level. The existence of non-performing loans faced by banks proves that banks must continue to maintain their prudence.